The role of network administrative organizations in the development of social capital in inter-organizational food networks - M. Lefebvre, Virginie; Molnár, Adrienn; Gellynck, Xavier (Acta Agraria Debreceniensis, 2012)
This paper is concerned with the role of network administrative organizations (NAOs) in the development of social capital in interorganizational networks aiming at supporting their members to innovate in the food sector through interacting with one another. A multi-case study approach is used whereby three Belgian interorganizational networks are investigated i.e. Wagralim, Réseau-Club and Flanders Food. Our study shows that there are many options available to NAOs to build social capital within the networks they are responsible for. We propose to categorize these options in three main distinct groups. First, NAOs may nurture the development of social capital within the network through creating ‘space’ boundary objects which appear, in our study, to be an absolute precondition for the development of interactions and hence creation of ties between network members. Second, NAOs may impact the development of social capital by favoring certain members – or set of members – over others due to their characteristics such as good reputation, possession of common past experiences, multidisciplinary experiences, non-conflicting goals, similarity in terms of sector of activity and/or experience level and common mindset towards information exchange. Third and finally, NAOs may foster social capital development by enhancing effective communication between members on the one hand, and between members and the NAOs’ coordination and decision bodies on the other hand, via a clear mandate, network decision making bodies composed of members, the use of ex-post evaluations and formal governance mechanisms (e.g. legal contracts), and the selection of staff endowed with a proactive and perspective taking behavior and able to show neutrality when conflict arise.